The Impact of a High-Altitude Expedition on the Physical Performance and Nutritional Indices of Health Status of Alpinists - Ewa Karpęcka-Gałka; Marek Bawelski; Aleksandra Pięta; Paulina Mazur-Kurach; Paweł Pięta; Barbara Frączek (Journal of Functional Morphology and Kinesiology)
Objective: The aim of the study was to determine the effect a mountain expedition (>3000 m) would have on the physical performance and nutritional indices of alpinists’ health status. Methods: The study included 17 men aged 30.29 ± 5.8 years participating in mountain expeditions to peaks of 5000–8000 m, lasting an average of 34 ± 6 days. The following were assessed: aerobic and anaerobic capacity, body composition and the values of selected biochemical and hematological indices of blood and urine before and after returning from the expeditions and a quantitative analysis of the alpinists’ diet. Results: There was a statistically significant decrease (p ≤ 0.05) in aerobic capacity, anaerobic capacity, subjects’ body mass, muscle mass and the lean body mass of the upper and lower extremities. There was a significant increase (p ≤ 0.05) in erythrocytes, hemoglobin, hematocrit, leukocytes, platelets, neutrophils, monocytes and a significant decrease (p ≤ 0.05) in total and high-density lipoprotein cholesterol, total bilirubin, albumin and total protein. A small percentage of the subjects met the requirements for iron (29.41%), folate (35.29%) and vitamin D (17.65%) supply with diet, as reflected in the blood test results. Conclusions: Despite the observed positive effect of three-week hypoxic exposure on the climbers’ health, the deterioration of aerobic and anaerobic capacity was shown, which, in addition to environmental conditions and systemic inflammation, may have been influenced by adverse changes in body composition. To improve the nutritional status of the body during the expedition and upon return, alpinists should consider including the necessary supplementation of deficient components.